Accelerating progress to end hunger and undernutrition in Bangladesh, Ethiopia, Malawi, and Rwanda - Compact2025 (International Food Policy Research Institute, 2018)
Compact2025 is a bold new initiative for ending hunger and undernutrition by 2025. It brings stakeholders together to set priorities, innovate and learn, fine-tune actions, build on successes, and synthesize sharable lessons in order to accelerate progress. Compact2025 and partners organized one-day roundtable discussions in Bangladesh (May 5, 2016), Ethiopia (March 28, 2016), Malawi (May 26, 2016), and Rwanda (March 24, 2016) to set the critical groundwork for assessing how to accelerate progress to end hunger and undernutrition in each country by 2025. The roundtables identified key knowledge, policy, and implementation gaps as well as opportunities, synergies, and priority areas for action. In all countries, there was a high degree of commitment, strong interest to work together across sectors, and out-of-the-box thinking for solutions to accelerate progress.